Water use in the Russian part of the Ural River basin and the reservoirs’ impact on the annual runoff - Dmitry V. Magritsky (Водное хозяйство России: проблемы, технологии, управление)
In conditions of significant long-term changes in river runoff and water regime, it is important to separate the contribution of climatic and anthropogenic factors to them. First of all, this applies to rivers in the most economically developed and arid regions, which have a great shortage of water resources. Among them is the Ural River, which in addition is trans-boundary watercourse and characterized by spatial-temporal distribution. Moreover, from 2006-2008 the hard low-water period was observed in the Ural River basin, the causes of which could be both climatic changes and water management activities.